A Systematic Literature Review on the Evolution of Marketing Research Practices - Richard Evans; Endah Kurniyaningrum; Nur Silawati (Startupreneur Business Digital (SABDA Journal), 2026)
The accelerating development of Artificial Intelligence (AI) and automation technologies has profoundly transformed the digital business ecosystem, catalyzing the emergence of cyberpreneurship as a dominant model of contemporary entrepreneurship. While AI enables unprecedented opportunities such as enhanced decision making, operational efficiency, personalized customer experience, and scalable business growth it simultaneously introduces critical challenges, including data privacy risks, algorithmic bias, digital inequality, and workforce displacement. This study systematically synthesizes existing research to examine the dualistic impact of AI and automation on cyberpreneurial opportunities and challenges. Employing a Systematic Literature Review (SLR) integrated with Bibliometric Analysis, 525 articles published between 2018 and 2025 were collected from Scopus and Web of Science. Bibliometric mapping using VOSviewer identified five core thematic clusters, technological innovation, business efficiency, digital transformation, startup ecosystems, and AI-driven marketing. The results highlight that AI-driven automation significantly enhances cyberpreneurial innovation and competitiveness, yet its adoption remains uneven due to technical, ethical, and socio economic constraints. This study concludes that future research should prioritize the development of adaptive, human centric frameworks that balance automation benefits with ethical considerations to ensure sustainable and inclusive cyberpreneurial growth in the AI-driven digital economy.